HUBUNGAN ANTARA PENGGUNAAN ALAT KONTRASEPSI HORMONAL SUNTIK DMPA DENGAN KENAIKAN BERAT BADAN DI BPM BIDAN ERLIKASNA, Amd.Keb - Munaf, Ardianti; Susanti, Rini (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
Contraception is an effort to prevent unwanted pregnancy; it can be either temporary or permanent. SDKI data at Riau Islands in 2007 showed that injected contraception was the most prominent method (50%). The objective of this study was to identify the correlation between use of injected DMPA hormonal contraception and weight gain. This is an analytical observation study with cross sectional approach. The study was done on June to July 2017. Population of the study consisted of 422 acceptors of DMPA injection visiting Erliksana Midwife Clinic in 2016. The sampling technique was accidental sampling. Data were analyzed by using chi square. 9 out of 35 respondents (52.9%) in less than 1 year use category revealed weight gain. On more than 1 year use category 16 respondents (88.9%) showed weight gain. The p value was 0.027. There was correlation between injected contraception use and weight gain. The midwives should give socialization about safe contraception use and about side effect of contraception.